2010
DOI: 10.3923/pjbs.2010.448.451
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coagulation State and its Related Factors in Thalassemia Intermedia Patients Referred to Thalassemia Research Center at Booali Sina Hospital Sari/IR Iran in 2007

Abstract: A high incidence of thromboembolic events have been reported among thalassemia intermedia patients especially in splenectomized patients. This study has been conducted to evaluate the coagulation state of patients referred to thalassemia research center at Booali Sina Teaching Hospital, Sari, Iran. This descriptive-cross sectional study was performed in 2007. Sixty thalassemia intermedia patients aged older than 10 years were enrolled. After recording demographic and therapeutic data of the participants, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
5
1
Order By: Relevance
“…Previous publications did not reach a uniform agreement regarding this point. While some researchers found similar results to ours [22,25], others found comparable levels when compared to normal individuals [8].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous publications did not reach a uniform agreement regarding this point. While some researchers found similar results to ours [22,25], others found comparable levels when compared to normal individuals [8].…”
Section: Discussionsupporting
confidence: 84%
“…No significant differences could be noticed between males and females regarding anticoagulants levels denoting that both sexes are at equal risk for TEE development. Apart from Karami et al [25] reporting lower levels among males, other studies did not find significant sex differences [27]. Although TEEs were reported much more in TI than TM patients [2,27], we could not find a significant difference in anticoagulants levels between both groups.…”
Section: Discussioncontrasting
confidence: 77%
“…Hassan et al 8 reported decreased levels of protein C and S in their study of 50 children with thalassemia in comparison to the control group. 9 Sipahi et al 10 reported that protein C, protein S, and AT-III were low in 26.2%, 28.6%, and 46.8% of their thalassemic patients, respectively. Shebl et al 11 in an Egyptian cohort of thalassemic patients, reported significantly decreased in levels of protein C and AT-III activity for all patients with thalassemia compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation proposed for decreased levels of protein C and protein S in thalassemic patients was that these proteins are very sensitive to even a mild degree of impairment of the synthetic function of the liver, which is a common occurrence in thalassemia due to various causes as hepatic hemosiderosis, viral infections, and vitamin and protein deficiency. 9 An alternative explanation for the significant reduction in protein C was its high affinity to bind to phosphatidyleserinea and other negatively charged phospholipids, which are abnormally present in the external membrane of the thalassemic erythrocytes. 12 Shirahata et al 13 found that liver damage was not the only cause of the reduction in these anticoagulant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Increased platelet aggregation due to increased platelet activation, and decreased platelet survival because of increased consumption, as well as urinary excretion of thromboxane A 2 and prostacyclin metabolites, have been identified in thalassemic patients [5,14]. Depletion of antithrombotic factors such as protein C and S [3,5,[15][16][17][18][19][20], lower antithrombin III levels [11,17,21], and low-grade chronic inflammation [22] might also play a role in the cause of hypercoagulable state. Other risk factors for thrombosis, particularly in patients with b-thalassemia intermedia, are splenectomy, age more than 20 years, family history and previous thromboembolic events [3,23,24].…”
Section: Introductionmentioning
confidence: 99%